An in vivo microscopy dataset for the characterization of leukocyte death - Alain Pulfer; Diego Ulisse Pizzagalli; Miguel Palomino Segura; Nina Germic; Tommaso Virgilio; Mauro Di Pilato; Pau Carrillo Barbera; Elisa Palladino; Paola Antonello; Marcus Thelen; Hans-Uwe Simon; Rolf Krause; et al. (Scientific Data)
Abstract Recent advancements in intravital microscopy have enabled the study of cell death in vivo under various experimental conditions, such as infection and cancer. However, the limited throughput of this technology, together with a lack of openly accessible datasets, affects the development of algorithms for the automatic detection and characterization of cell death, which in turn require the integration of extensive and curated datasets. To address these needs, we present a curated dataset of microscopy videos depicting the death of neutrophils, eosinophils, and dendritic cells, acquired in the spleen and in the lymph node of mice under inflammatory conditions. The dataset provides time-lapse imaging data, along with coordinates in space and time of cell death events displaying apoptotic–like morphodynamics, and 3D reconstruction of the cell morphology at each time point. Altogether, these data will be pivotal for developing computer vision and bioimage analysis methods to advance cell death research.